Induction of tolerance to immunogenic tumor antigens associated with lymphomagenesis in HOX11 transgenic mice - Rosic-Kablar, Suzana (The National Academy of Sciences, 2000)
Transgenic mice expressing human HOX11 in B lymphocytes die prematurely from lymphomas that initiate in the spleen and frequently disseminate to distant sites. Preneoplastic hematopoiesis in these mice is unperturbed. We now report that expression of the HOX11 transgene does not affect the ability of dendritic cells (DCs) to process and present foreign peptides and activate antigen-specific T cell responses. We also show that nontransgenic DCs presenting peptides derived from the human HOX11 protein are highly efficient stimulators of autologous T cells, whereas transgenic T cells are nonresponsive to peptides derived from the HOX11 transgene and the murine Meis1 protein. HOX11 transgenic mice thus show normal development of tolerance to immunogenic antigens expressed throughout B cell maturation. DCs pulsed with cell lysates prepared from lymphomas, obtained from HOX11 transgenic mice with terminal lymphoma, activate T cells from nontransgenic and premalignant transgenic mice, whereas T cells isolated from lymphomatous transgenic mice are nonresponsive to autologous tumor cell antigens. These data indicate that HOX11 lymphoma cells express tumor-rejection antigens that are recognized as foreign in healthy transgenic mice and that lymphomagenesis is associated with the induction of anergy to tumor antigen-specific T cells. These findings are highly relevant for the development of immunotherapeutic protocols for the treatment of lymphoma.